2020
DOI: 10.1080/01658107.2020.1810286
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing Optic Disc Drusen in the Modern Imaging Era: A Practical Approach

Abstract: Optic disc drusen (ODD) are a well-recognised cause of an elevated optic disc appearance. When visible with ophthalmoscopy and fundus photography, ODD are readily identified. Yet, in more subtle cases of ODD, ancillary testing may be needed to render the diagnosis. Facilitating the diagnosis of ODD has clinical relevance, because affected individuals may otherwise undergo unnecessary costly and invasive investigations to rule out raised intracranial pressure and other causes of optic disc oedema. In this revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 41 publications
(103 reference statements)
0
22
0
Order By: Relevance
“…5 Interestingly the HHL has also been reported to be the precursors of ONHD as they are also reportedly common in children. 22 They are often found in children with drusen and might represent early drusen in evolution. Lasse Malmquist et al have reported that super cial drusen were found in older age groups and median age for deep drusen was 21 years.…”
Section: Discussionmentioning
confidence: 99%
“…5 Interestingly the HHL has also been reported to be the precursors of ONHD as they are also reportedly common in children. 22 They are often found in children with drusen and might represent early drusen in evolution. Lasse Malmquist et al have reported that super cial drusen were found in older age groups and median age for deep drusen was 21 years.…”
Section: Discussionmentioning
confidence: 99%
“…We do recommend though, that OCT imaging of the deep structure of the optic disc-and not only the peripapillary nerve fibre layer-be included in routine OCT investigation. As the gold standard diagnostic for superficial and deep ODD, the international Optic Disc Drusen Studies Consortium recommends a dense 97-lines OCT covering the entire optic disc with enhanced depth imaging enabled and b-scan averaging of 30 or more (Costello et al 2020). ODD should be on the list of abnormalities that are looked for by OCT imaging and an appropriate scan protocol.…”
Section: Discussionmentioning
confidence: 99%
“…While large, superficial accumulations often protrude and lead to the characteristic changes that can be diagnosed by biomicroscopy, smaller and deeper located ODD are hard to detect (Costello et al. 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although many hyper-reflective lines occur in isolation, sometimes they are associated with very small ODD that can be missed by OCT scans. 32,33 The optical properties that give rise to the hyper-reflective horizontal lines on OCT may also be a strong ''reflector'' on NIR. A few reports have described PHOMS in association with ODD on OCT B-scan.…”
Section: Imaging Modalities In Diagnosis Of Oddmentioning
confidence: 99%